Yang Hak-Seong's gold project in vault of gymnastics in London 2012 Olympics - Song, J.-H. (Asian Conference on sport science. Sport science and elite training programme for world class performance. 25-26 October 2013. Hong Kong Sports Institute, Hong Kong, China, 2013)
This study was to analyze a Korean national gymnastic athlete, Yang Hak-Seon`s technique in vault by carrying out kinematic analysis through a high speed camera system with three dimensional video analyses. We found out main variables to conduct a successful performance by comparing and analyzing his movement when he attended three evaluation tests in 2012. The first test was T2 which he slipped forward while landing on the mat in April 2012. The second test was T1 which he failed to stick the landing in May, 2012 and third test was T3 when he performed successfully in July, 2012. First, when he performed the T3 movement, he maintained hip height of staying in the air as 2.48m during the second leap phase and maintained the duration of his air time as 1.07 seconds. He showed the angle of trunk rotation as 460 degrees when he reached the peak performance. He kept the trunk twist rotational velocity as 1349 deg/s which was very fast. Secondly, he achieved faster rotational velocity of trunk twist on downward phase than upward phase during the second leap phase. When it came to the rotational velocity of trunk twist, T3 had the faster movement than T2 and T1 on upward phase, however, T3 showed slower movement on downward phase. Third, the angle of trunk rotation was 37 degrees and the time that he got to the vault was 0.15 seconds which was the fastest. Rotational velocity of the thigh for take-off the vault was 231 deg/s and rotational velocity of the trunk was 634 deg/s to maintain a successful rotational movement in the air. Finally, he maintained the angle of hip twist line as when he performed T3 movement for the peak on the second leap phase. He folded arms then uncross them to extend the radius of rotation and ultimately controlled the landing movement.